Contribution to the dynamic study of a rotor by finite elements - AIMEUR Noureddine (University of M'Sila, 2024)
Rotor dynamics is an important aspect of the design or analysis of any type of rotating machine, as various types of vibrations appear in this mechanical system when the rotor is turned on, which can limit performance or easily lead to disaster. Therefore, the dynamic analysis of the rotor is necessary to ensure proper operation by providing accurate knowledge of the vibration behavior of the rotor system. In this study, scientific techniques for modeling and simulating the vibrations of a rotating system are presented. The equations of vibration motion of the rotor are determined using the Lagrange energy method. The centrifugal fan installed at the cement factory was selected to be of the FN280 type, equipped with a single wheel with blades mounted on the shaft supported by two bearings. Due to the fact that the manual solution of the equations of motion characterizing the dynamic analysis is considered a difficult task, the dynamic analysis of the cement fan FN280 using the finite element method was performed by the code ANSYS. The various components of the fan are designed using SolidWorks, except for the blade. Due to the lack of design data for it, we resorted to reverse engineering technology, which is also called reverse design. To obtain a 3D model of the blade, we used a CMM machine to scan the blade, and the fan was assembled and a dynamic analysis of the rotor was performed using the ANSYS Workbench. We determined the natural frequencies, extracted the critical speed by means of the Campbell diagram and mode shapes, and also studied the effect of the worn blades on dynamic behavior. In addition, a harmonic response analysis was performed in both cases. FSI simulation was also applied to the fan to estimate the loads resulting from unsteady flow. This simulation process is carried out using the ANSYS Workbench, which integrates flow simulation and transient analysis simulation using a one-way coupling approach. This approach was chosen because there is very weak interaction between the structural domain and the fluid. The purpose of this simulation is to verify the ability to make a preliminary estimate of the fatigue limit and the effect of pressure loads applied to the structure resulting from unsteady flow on the life of the fan. Results showed that air loads have a negligible effect on fan life.
تعت ر برر ي رتصميم ديناميكياترالدواررمنرالاموررالمهمةرف راورتحليلرأيرنوعرمنرالآلاترالدوارةر،رحيثرتظهررأنواعرمختلفةر ي رهذارالنظامرالميكاني ي كرعندرتشغيلرالدوارر،رممارقدريحدرمنرالأداءرأوريمكنرأنريؤديربسهولةرإلىركارثة.رلذلكر،ر منرالاه بازاتر ف يعدرالتحليلرالدينامي ي كرللدوارر ضوريار لضمانرالتشغيلرالسليمرمنرخلالرتوف ربرمعرفةردقيقةربالسلوكرالاه بازيرلنظامرالدواررر ي رهذهرالدراسةر، .ف ريتمرتقديمرتقنياترعلميةرلنمذجةرومحاكاةراه بازاترالنظامرالدوار.رريتمرتحديدرمعادلاترالحركةرالاه بازيةر للدواررباستخدامرطريقةرطاقةرلاغرانج.ر ر ي رمصنعرالأسمنترمنرنوعر ر،ر ر والمجهزةربعجلةرواحدةرذاترشفراترر FN تمراختياررمروحةرالطردرالمركزيرالمثبتةر ف 280 مثبتةرعلىرالعمودرالمدعومربمحمل ر ي.رنظرارلحقيقةرأنرالحلراليدويرلمعادلاترالحركةرال ي ترتم ر برالتحليلرالدينامي ي كريعت برمهمةر ررباستخدامرطريقةرالعناضرالمحدودةربواسطةر برنامجر FN صعبة،رفقدرتمرإجراءرالتحليلرالدينامي ي كرلمروحةرالأسمنترر 280 ر،رباستثناءرشفرة.رلعدمروجودربياناترتصميمر SOLIDWORKS رر.رتمرتصميمرالمكوناترالمختلفةرللمروحةرباستخدامرر ANSYS ي رالأبعادرللشفرةرر ر،رللحصولرعلىرنموذجرثلا ث ي رتسمىرأيضارالتصميمرالعك ي س لها،رلذلكرلجأنارإلىرتقنيةرالهندسةرالعكسيةر،روال ت ر ANSYS ررلمسحرالشفرةر ر وتمرتجميعرالمروحةروإجراءررالتحليلرالدينامي ي كرللدوا ر ررباستخدامرمنصةر CMM قمنارباستخدامرآلةر رررحددنارال بدداترالطبيعية,ر ر واستخرجناررالسرعاترالحرجةرعنرطريقرمخططركامبلر ر وأشكالرالوضع,رودرسنار .WORKBENCH ايضارتأث ربرالشفرةررالمتأكلةررعلىرالسلوكرالدينامي ي ك.ربالإضافةرإلىرذلكر،رتمرإجراءرتحليلرالاستجا ي ركلتارالحالت ر ي.رر بةرالتوافقيةر ف ررعلىرالمروحةرمنر أجلرتقديررالأحمالرالناتجةرعنرالتدفقرغ ربرالمستقر.ررحيثريتمرإجراءرر FSI كماررتمراجراءرمحاكاةر رر،رالذيرريدمجرمحاكاةرالتدفقرومحاكاةرالتحليلرالعابررباستخدامرنهجر ANSYS WORKBENCH عمليةرالمحاكاةرهذهرباستخدامرر اق بانرأحاديرالاتجاهروتمراختياررهذرارالنهجرلوجودرتفاعلرضعيفرجدارب ر يرالمجالرالهيك ي لىروالسائل.رالهدفرمنرهذهرالمحاكاة،رر هورالتحققرمنرالقدرةرعلىرعملرتقديررأو ي لىرلحدرالتعبروتأث ربرأحمالرالضغطرالمطبقةرعلىربنيةرالمرر وحةرالناتجةرعنرالتدفقرر غ ربرالمستقررعلىرحياةرالمروحة.رأظهرترالنتائجرأنرأحمالرالهواءرلهارتأث ربرعلىرعمررالمروحةر،رراظهرترالنتائجرانراحمالرالهواءر لهارتاث ربرضئيلرعلىرعمررالمروحة.ررر